Boletaceae in China: Taxonomy and phylogeny reveal a new genus, two new species, and a new record - Wang, Yang; Wang, Li-Ying; Dai, Dan; Qi, Zheng-Xiang; Zhang, Zhen-Hao; Liu, Ya-Jie; Hu, Jia-Jun; Zhang, Peng; Li, Yu; Zhang, Bo (Frontiers in Microbiology, 2023)
Boletaceae, the largest family in Boletales, is attracted by world due to its diverse morphology and complex history of evolution. Although considerable work has been done in the past decades, novel taxa are continual to be described. The current study aimed to introduce three new taxa and one new record of Boletaceae from China. The morphological descriptions, photographs, illustrations, phylogenetic positions, and allied taxa’s comparisons were listed. The new genus Hemilanmaoa is unique in Pulveroboletus group, and Hemilanmaoa decurrens was introduced as type species. It can be distinguished by its basidiomata changing to blue when injured, hymenophores decurrent, stipe covered with distinctly reticulations and stipitipellis fertile. Porphyrellus pseudocyaneotinctus is characterized by its pileipellis consisting of broadly concatenated cells and caulocystidia thin-walled in Porphyrellus. In Phylloporus, Phylloporus biyangensis can be distinguished by its hymenophores changing to blue when injured, basal mycelium yellow, and basidiospores with bacillate ornamentation. Lanmaoa angustispora, as a new record species, is first reported in Northern China. Internal transcribed spacer (ITS), 28S rDNA (28S), translation elongation factor 1-alpha (tef1-α), RNA polymerase II subunit 1 (rpb1), and RNA polymerase II subunit 2 (rpb2), were employed to execute phylogenetic analyses.